Centrifuge scaling laws of pile response to lateral spreading. Issue 1 (March 2011) - Ubilla, J.; Abdoun, T.; Dobry, R.
Abstract : A number of centrifuge tests have been conducted to study the interaction between liquefied sand under earthquake-induced lateral spreading and pile foundations. Most of those centrifuge models resemble full-scale prototypes from case histories, usually with limited field measurements, while a few of them replicate the conditions of full-scale heavily instrumented laboratory tests. This paper presents the results of centrifuge tests modelling the single pile interaction with liquefied sand conducted at Rensselaer Polytechnic Institute in Troy, New York, and their comparison with the respective large-scale prototype tests conducted at the National Research Institute for Earth Science and Disaster Prevention in Tsukuba, Japan. A critical analysis of the scaling laws currently used for this kind of centrifuge tests is included, focusing on the use of viscous fluid for centrifuge model saturation and the validity of the centrifuge scaling laws when shear band development plays an important role in soil–structure interaction. This paper also presents recommendations for pile foundations design against the lateral pressure associated with liquefied sand under lateral spreading.